2020
DOI: 10.3390/nu12092629
|View full text |Cite
|
Sign up to set email alerts
|

Nettle Tea Inhibits Growth of Acute Myeloid Leukemia Cells In Vitro by Promoting Apoptosis

Abstract: Urtica dioica (UD), commonly known as “stinging nettle”, is a herbaceous flowering plant that is a widely used agent in traditional medicine worldwide. Several formulations of UD leaf extract have been reported to exhibit anti-inflammatory and antioxidant properties, with anticancer potential. The current study investigated the possible anticancer properties of nettle tea, prepared from Urtica dioica leaves, on acute myeloid leukemia (AML) cell lines, and deciphered the underlying molecular mechanisms. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Increased Bax/Bcl-2 ratio up-regulates caspase-3 activity and subsequently triggers programmed cell death in cancer cells [ 42 ]. Numerous literature have documented an important regulatory role of phytochemicals in Bax/Bcl-2/caspase-3 signaling in breast carcinogenesis [ 43 , 44 , 45 ]. This experiment clearly shows a significant dose-dependent increase in the Bax/Bcl-2 ratio in rat mammary tumors induced by sumac treatment, which correlates with an increase in cleaved caspase-3 expression in the treated group and higher sumac dose.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Bax/Bcl-2 ratio up-regulates caspase-3 activity and subsequently triggers programmed cell death in cancer cells [ 42 ]. Numerous literature have documented an important regulatory role of phytochemicals in Bax/Bcl-2/caspase-3 signaling in breast carcinogenesis [ 43 , 44 , 45 ]. This experiment clearly shows a significant dose-dependent increase in the Bax/Bcl-2 ratio in rat mammary tumors induced by sumac treatment, which correlates with an increase in cleaved caspase-3 expression in the treated group and higher sumac dose.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition to its antimicrobial effects, PHBA has been reported to possess a dose-dependent cytotoxic effect on prostate (PC-3), breast (MCF-7), and leukemic cancer cells. 8,9 PHBA has also been found to have an antihyperglycemic effect 10 in addition to its protective effect against atherosclerosis, inflammation, allergy, myocardial damage, and thrombosis. 11 Furthermore, PHBA and its derivatives 3, 4, 5-trihydroxybenzoic acid, ellagic acid, gallic acid, and pyrogallic acid are important molecules in the medicinal chemists' search for effective and safe molecules with antialgal activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its antimicrobial effects, PHBA has been reported to possess a dose‐dependent cytotoxic effect on prostate (PC‐3), breast (MCF‐7), and leukemic cancer cells 8,9 . PHBA has also been found to have an antihyperglycemic effect 10 in addition to its protective effect against atherosclerosis, inflammation, allergy, myocardial damage, and thrombosis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Urtica is rich in essential amino acids and minerals, as well as vitamins C, B, and K. Because of the huge nutritional value, urtica has been listed as a natural source of food flavorings in Europe and supplemented in soups and herbal teas (Joshi et al, 2014). Mohammad et al found that urtica extracts inhibit the growth of acute myeloid leukemia cells in vitro by promoting apoptosis (Hodroj et al, 2020). Both in vitro and in vivo proliferation of breast cancer cells can be suppressed by urticaria extracts, and they also enhance the sensitivity of paclitaxel drugs to breast cancer cells (Mohammadi et al, 2017) (Mohammadi et al, 2016).…”
mentioning
confidence: 99%